Method and System for Automatically Generating Multilingual Electronic Content from Unstructured Data - Emam, Ossama; Hassan Awadalla, Hany; Yassin, Amr (2005)
The present invention is directed to the field of electronic content management and more particularly to a method, system and computer program for automatically generating electronic content based on a user designed table of contents and a desired final content form. Language identification and automatic machine translation technologies are also used to broaden the sources of information, The method comprises the steps of: extracting from the unstructured data, information related to one or a plurality of preselected topics; consolidating the extracted information in a structured form; localizing the consolidated information according to a selected environment; generating content according to a specified form.
US20070156748A1 US Application